Alpha-interferon maintenance treatment is associated with improved survival after high-dose treatment and autologous stem cell transplantation in patients with multiple myeloma: a retrospective registry study from the European Group for Blood and Marrow Transplantation (EBMT) - Björkstrand, Bo; Svensson, H.; Goldschmidt, Hartmut; Ljungman, P.; Apperley, J.; Mandelli, F.; Marcus, R.; Boogaerts, M.; Alegre, A.; Remes, K.; Cornelissen, J. J.; Bladé, J.; et al. (Bone marrow transplantation, 2001)
The purpose of this study was to evaluate the effect of alpha-IFN maintenance treatment after autologous stem cell transplantation (ASCT) for multiple myeloma in a retrospective registry analysis. 473 patients with multiple myeloma who received IFN maintenance treatment ASCT were compared with 419 patients who did not receive IFN-treatment. Patients who were evaluable for response and in complete or partial remission at 6 months after ASCT were eligible, after excluding patients with graft failure. Cox proportional hazards assumptions were checked and handled by stratification. The prognostic variables unevenly distributed between the two groups were statistically corrected for in the Cox analysis. 391 patients reached complete remission (CR) after ASCT (203 in the IFN group and 188 in the no-IFN group) and 501 were in partial remission (PR, IFN 270, no-IFN 231). Overall survival (OS) and progression-free survival (PFS) were significantly better in the IFN-group (OS, 78 vs 47 months, P = 0.007, and PFS, 29 vs 20 months, P = 0.006, respectively). The difference in OS and PFS was most strongly pronounced in the PR patients. 209 patients have died (IFN, 84; no-IFN, 125). Progressive myeloma was the cause of death in 94% of the IFN-treated patients and in 83% of the no-IFN group (P = NS). Thus, IFN maintenance treatment after ASCT was associated with better OS and PFS. Treatment seemed to be most beneficial in patients who did not achieve CR. The difference in median survival was as long as 2.5 years, and although part of this difference is attributable to differences in other prognostic factors, it might justify possible differences in quality-of-life due to adverse effects of interferon treatment. Bone Marrow Transplantation (2001) 27, 511-515.
Gesehen am 01.03.2022